Subversion of innate immune responses by Francisella involves the disruption of TRAF3 and TRAF6 signalling complexes - Putzova, Daniela; Panda, Swarupa; Härtlova, Anetta; Stulík, Jiří; Gekara, Nelson O (Cellular microbiology, 2017)
The success of pathogens depends on their ability to circumvent immune defences. Francisella tularensis is one of the most infectious bacteria known. The remarkable virulence of Francisella is believed to be due to its capacity to evade or subvert the immune system, but how remains obscure. Here, we show that Francisella triggers but concomitantly inhibits the Toll-like receptor, RIG-I-like receptor, and cytoplasmic DNA pathways. Francisella subverts these pathways at least in part by inhibiting K63-linked polyubiquitination and assembly of TRAF6 and TRAF3 complexes that control the transcriptional responses of pattern recognition receptors. We show that this mode of inhibition requires a functional type VI secretion system and/or the presence of live bacteria in the cytoplasm. The ability of Francisella to enter the cytosol while simultaneously inhibiting multiple pattern recognition receptor pathways may account for the notable capacity of this bacterium to invade and proliferate in the host without evoking a self-limiting innate immune response.
Keywords: Animals; přirozená imunita; Francisella tularensis; Immune Evasion; Adaptor Proteins, Vesicular Transport; ubikvitinace; Receptors, Pattern Recognition; Adaptor Proteins, Signal Transducing; Mice, Knockout; myši knockoutované; adaptorové proteiny signální transdukční; tularemie; myeloidní diferenciační faktor 88; Mice; Myeloid Differentiation Factor 88; sekreční systém typu VI; Tularemia; Type VI Secretion Systems; myši; faktor 6 asociovaný s receptory TNF; TNF Receptor-Associated Factor 6; faktor 3 asociovaný s receptory TNF; Immunity, Innate; Ubiquitination; imunitní únik; TNF Receptor-Associated Factor 3; zvířata; receptory rozpoznávající vzory; Mice, Inbred C57BL; adaptorové proteiny vezikulární transportní; myši inbrední C57BL